QUALITY EVALUATION OF SANDCRETE BLOCKS PRODUCED IN SELECTED LOCAL GOVERNMENT AREAS OF KADUNA STATE, NIGERIA (Nigerian Journal of Technology, 2025)
Nigeria has witnessed problems in the construction industry such as the collapse of buildings which is a consequence of the use of substandard materials in building construction, poor supervision, negligence to standard code of practice, poor maintenance culture, and faulty design amongst others. Quality assurance and quality control are highly imperative to take cognisance of while examining building companies. This research examined the quality of nine-inch hollow concrete blocks produced using machine moulding in Kaduna Metropolis, which includes Kaduna North, Kaduna South, parts of Igabi, and parts of Chikun Local Government Areas in Kaduna State. The study employed a mixed research design method comprising experimental design and interviews. The result of the laboratory test carried out on the blocks showed the mean compressive strength of the blocks ranges from 0.21N/mm2 to 0.62N/mm2 which does not meet the minimum of 1.6N/mm2 compressive strength provided by the Nigerian Industrial Standard (NIS) 87:2000. The bulk densities of the samples tested range from 1286kg/m3 to 1537kg/m3 and are below the minimum of 1,800kg/m3 provided by NIS 87:2000. The result of the interview conducted across 32 block industries showed a complete ignorance of standards as block industries determine their standard based on market forces. Only 3% of the block industries complied with the mix ratio of 20-25 blocks per one bag of cement, and less than 10% carried out quality assurance checks such as weekly inspection of mould for wear and tear and taking measurements of the dimensions to ensure that it meets the standard. In all, only one of the block industries provided evidence of certification from the Standard Organisation of Nigeria (SON). The study further underscored the urgent need for enforcing industry standards in the production of hollow sandcrete blocks in the Kaduna metropolis.